An Alternative Approach to Estimating Brand Attraction Share: A Quantitative Comparison with the Colombo Morrison Model - Miladi, Jalal (Journal of Global Economy, Business and Finance, 2026)
Brand Studies have concentrated on choices made by buyers between brands and their impact on market shares of such brands. Most models measure purchase distributions by forming conditional probability tables or brand switching matrices (BSM). Largely such matrices consider the “first order” model condition of brand switching wherein probability of occurrence of any given outcome at a particular point in time depends on any previous outcomes of the buying process. Thus, market share of a brand is built by its attraction share i.e., the ability to of the brand to appeal buyers of other brands and its gravity share i.e., the ability of the brand to hold its current buyers from moving towards other brands. The process can be described as “inflow-outflow and steady state (I-O & S)” usage of buyers which is the cornerstone of “focus” and “gravity” share concept proposed by Colombo Morrison (C_M) in their paper published in Marketing Science,1989(1). Their treatise considers focus as “appeal” or “attraction” and gravity as “retention” or “loyalty” stemming from the I-O & S state of users. The C_M model is based on deriving “attraction” and “loyalty” shares by directly using conditional probabilities (obtained in the BSM) by proportional draw method. This paper proposes to represent an alternate view of estimating “attraction” share through Pi transformation of the conventional BSM probabilities. All other estimations of the original C_M model and its theoretical objective remain unchanged. In conclusion, the paper compares the results obtained for “attraction” and “loyalty” shares under both scaling practices for similarity and validity.